Mass transfer in the Frenkel-Kontorova chain initiated by molecule impact - Babicheva, Rita I. (2018)
The Frenkel-Kontorova chain with a free end is used to study initiation and propagation of crowdions (antikinks) caused by impact of a molecule consisting of K atoms. It is found that molecules with 1<K<10 are more efficient in the initiation of crowdions as compared to a single atom (K=1) because the total energy needed to initiate the crowdions by molecules is smaller. This happens because a single atom can initiate in the chain only sharp, fast-moving crowdions that require relatively large energy. A molecule has finite length, and that is why it is able to excite a wider crowdion with a smaller velocity and smaller energy. Our results can shed light on the atomistic mechanisms of mass transfer in crystals subject to atom and molecule bombardment.